Incidence and factors associated with hypotension in emergency patients that underwent cesarean section with spinal anaesthesia: Prospective observational study. (September 2021) - Chekol, Wubie Birlie; Melesse, Debas Yaregal; Mersha, Abraham Tarekegn
Abstract: Background: Hypotension is the common incidental complication after subarachnoid block in emergency cesarean section. This study aimed to identify incidence and factors associated with hypotension in emergency cesarean section that underwent spinal anaesthesia. Methods: Prospective observational study was done with statistical analysis of SPSS version 20. Binary logistic regression analysis was performed to determine whether each of independent variables was associated or not with the outcome variables. Both Crude and Adjusted Odds Ratio were calculated to show strength of association. Variables with P-value of <0.05 were considered to be statistically significant. Results: Incidence of hypotension in emergency cesarean section was 56.8% (95% CI; 50.2–63.4). Baseline systolic blood pressure <120 mmhg (AOR, 3.60 95% CI; 1.26–10.31), absence of spinal additives (AOR, 5.08, 95% CI; 1.78–14.48), duration of crystalloid load before 20 min (AOR, 27.9, 95% CI; 8.3–93.6) and speed of injection < 10 s (AOR, 4.47, 95% CI; 1.14–17.62) were significantly associated with hypotension. Conclusion: The incidence of hypotension was high. Baseline blood pressure, spinal additives, duration of crystalloid load and speed of injection were significantly associated with hypotension. So, we recommend considering spinal additives, fluid co-loading and slow injection of drugs to reduce incidence of hypotension. Highlights: The incidence of hypotension was high compared with previous literature. Baseline blood pressure, spinal additives and speed of injection were predictive factors. The study recommend to use spinal additives, fluid coloading and slow injection local anesthetics.